Isolated fallopian tubal torsion: Reproductive age case series - (:unkn) unknown (WILEY, 2021)
Aim To present our experiences in isolated fallopian tubal torsion (IFTT) case series, which are difficult to diagnose, in light of the literature. Methods The data of the patients diagnosed with IFTT surgically in our tertiary hospital between 2018 and 2019 were evaluated. Results Abdominal lower quadrant pain was present in all nine cases. Abdominal pain was accompanied by nausea in five of the nine cases with vomiting in four of the nine cases. Seven of the patients had pain radiating to the vagina. Only one case of IFTT was diagnosed with transvaginal ultrasonography where left tubal dilation and free fluid in the abdomen was found. Two of the nine cases were operated on with a preoperative diagnosis of IFTT. Seven cases were approached laparoscopically and two cases underwent a laparotomy. During the treatment, two of the nine cases underwent detorsion, while seven of the patients underwent a salpingectomy. Conclusion IFTT is a very rare condition. Therefore, it is difficult to diagnose as it does not come to mind at first glance. Delay of the operation reduces the chance of preserving the tube.
Keywords: fallopian tube torsion; isolate; rare cases; reproductive age